IMPACT OF CLIMATE CHANGE ON SANITARY–HYGIENIC INDICATORS AND ADAPTIVE MANAGEMENT SYSTEMS IN UZBEKISTAN - Raximov Baxodir; Sultonov Erkin; Malika Ro’ziyeva; Nizomova Durdona; Rustamova Gulnoza; Baxtiyorov Bekzodjon (Bright Mind Publishing, 2025)
Climate change has emerged as one of the most significant global challenges of the 21st century, exerting profound effects on environmental quality, public health, water security, infectious disease dynamics, and sanitary–hygienic stability, particularly in climate-sensitive regions such as Central Asia. Uzbekistan, characterized by arid and semi-arid climate zones, limited freshwater resources, high evapotranspiration, and rapid socio-economic transformations, is increasingly vulnerable to climate-driven shifts in sanitary–hygienic indicators that shape population health and environmental safety. This study presents a comprehensive analysis of how rising temperatures, intensified droughts, extreme weather events, atmospheric pollution, desertification, and water scarcity interact to alter water quality parameters, microbiological contamination patterns, food hygiene risks, air sanitation levels, and vector-borne disease propagation in Uzbekistan. Utilizing an integrated methodological approach that encompasses environmental sampling, spatiotemporal trend analysis, climate modeling, microbial risk assessment, and adaptive-system design, the study evaluates the current and projected impacts of climate change on sanitary–hygienic conditions and formulates evidence-based adaptive management frameworks suitable for national implementation. Findings reveal strong correlations between climatic variables and sanitary deviations, including increased microbial loads in surface waters during heatwaves, elevated particulate-matter concentrations facilitating bioaerosol spread, reduced water-treatment efficiency under high temperatures, and accelerated spoilage rates of perishable foods due to thermal shifts. Additionally, long-term projections suggest that without adaptive interventions, Uzbekistan could experience a 20–40% rise in climate-driven hygienic risks by 2050. The study proposes a multidimensional adaptive management system incorporating early-warning surveillance, climate-informed risk forecasting, sustainable water-resource governance, improved heat-resilient sanitation infrastructure, hygiene-oriented public-health education, and digital monitoring platforms capable of real-time hazard detection. The research contributes a novel conceptual and operational framework for integrating climate resilience into national sanitary–hygienic policy and underscores the need for cross-sectoral collaboration to safeguard public health in a warming climate.
Keywords: Climate Change, Sanitary–Hygienic Indicators, Uzbekistan, Environmental Health, Adaptive Management Systems, Microbiological Safety, Water Quality, Public Health Risk.